Aquagenic pruritus in essential thrombocythemia is associated with a higher risk of thrombosis. (8th September 2019) - Le Gall‐Ianotto, Christelle; Le Calloch, Ronan; Couturier, Marie‐Anne; Chauveau, Aurélie; Lippert, Eric; Carré, Jean‐Luc; Misery, Laurent; Ianotto, Jean‐Christophe
Abstract: Background: Thromboses and phenotypic evolutions (leukemia, myelofibrosis) are the most frequent complications in polycythemia vera (PV) and essential thrombocythemia (ET). Aquagenic pruritus (AP) is not only PV symptom, but is also present in ET. The presence of pruritus in PV is associated with a lower risk of arterial thrombosis. Aims: To date, no equivalent study has been done to analyse the impact of AP for ET patients. Materials & Methods: We used the data from our cohort of patients with myeloproliferative neoplasms seen in our institution (OBENE database, NCT02897297). We collect information at diagnosis, presence or not of AP and all types of complications during their follow‐up. To avoid masked PV, all JAK2 positive cases were tested isotopic red mass cell if appropriate. Results: Among 396 ET patients, presence of AP was found in 42 (10.6%). ET patients with AP were more proliferative, more symptomatic at diagnosis and more difficult to treat. Furthermore, they presented increased risk of thromboses (30.9 versus 17%, P = .03; OR = 2.2 [1.01;4.66]) and phenotypic evolutions (33.3 versus 13.3%, P = .0007; OR = 3.2 [1.44;6.77]), during follow‐up. Discussion: Aquagenic pruritus is classically associated to PV. But we confirmed here that AP is also present in ET and characterizes patients with higher risk of morbidity (thrombotic events and phenotypic evolutions). Conclusions: The systematic determination of the presence of AP in ET patients should permit us to better identify these high‐risk patients for better management and follow‐up.